Citizen's charter - An instrument of public accountability: Problems and prospects in India - Jain, R.B. (1998)
The author reviews the changing notions of accountability of Government towards its citizens in different nations and examines the strategy of enforcing Citizen's Charter as it evolved in the UK, giving key principles and elements of setting of charters. He then critically examines the post-1995 process of its adoption in India, giving his assessment on its strong and weak points. While concluding, he delineates on the measures that are necessary for the success of Citizen's Charter scheme in India. - Reproduced
Keywords: Citizen's charter - India; Public administration - India; Accountability - India; Citizen's charter